2004
DOI: 10.1002/anie.200453963
|View full text |Cite
|
Sign up to set email alerts
|

The Exclusivity of Multivalency in Dynamic Covalent Processes

Abstract: Natures reliance on multivalency [1] as a means [2] of compensating for weak monovalent protein-ligand interactions is now a widely accepted phenomenon [3] which controls a panoply of biological events and whose delicate manipulations could have far-reaching therapeutic implications. In recent times, the physical basis of multivalency effects, based on a thermodynamic model combined with computational studies, has been explored rigorously [4] and a comprehensive thermodynamic investigation of the calcium-EDTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The relevant intramolecular metathesis condensation of a linear poly(THF) having allyl end groups has been recently performed under dilution in the presence of a Grubbs catalyst, ruthenium( II ) dichloride phenylmethylene bis(tricyclohexylphosphine) [RuCl 2 (PCy 3 ) 2 (CHPh)], to produce a cyclic poly(THF) effectively 14. It is also worth noting that the intramolecular metathesis condensation of small‐ to medium‐size molecules having multiple olefinic groups has been employed for the construction of a variety of complex loop topologies 15–18…”
Section: Introductionmentioning
confidence: 99%
“…The relevant intramolecular metathesis condensation of a linear poly(THF) having allyl end groups has been recently performed under dilution in the presence of a Grubbs catalyst, ruthenium( II ) dichloride phenylmethylene bis(tricyclohexylphosphine) [RuCl 2 (PCy 3 ) 2 (CHPh)], to produce a cyclic poly(THF) effectively 14. It is also worth noting that the intramolecular metathesis condensation of small‐ to medium‐size molecules having multiple olefinic groups has been employed for the construction of a variety of complex loop topologies 15–18…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dynamic covalent chemistry (37)(38)(39)(40), exemplified by reversible imine formation (41,42), metal-ligand exchange (43), and olefin metathesis (44,45), has been demonstrated to be an effective tool for the preparation of various exotic mechanically interlocked molecular compounds. It has been found that, in the presence of an appropriate template, one of the possible compounds in the dynamic library, after mixing the different components, can be amplified to give the thermodynamically most stable product.…”
mentioning
confidence: 99%
“…Many reversible reactions, including the formation of imines, disulfides, and cyclic acetals, as well as olefin metatheses, have been employed as the final reaction steps to synthesize catenanes and rotaxanes 10. Especially, the construction of magic‐ring catenanes5c and magic‐rod rotaxanes11 by olefin metathesis has been recently reported. However, synthesis of more complex interlocked molecules by means of the DCC strategy is still a challenge.…”
Section: Methodsmentioning
confidence: 99%